2020
DOI: 10.1111/desc.13037
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in mothers’ spatial language use and children’s mental rotation abilities in Preschool and Kindergarten

Abstract: Mental rotation has emerged as an important predictor of success in Science, Technology, Engineering, and Math (STEM). By the age of 4.5 years, boys outperform girls in these abilities. Because parents use less spatial language with girls at this age (Pruden and Levine, 2017), the amount of spatial language that children are exposed to at home is believed to be one potential contributor to this disparity in preschool age children. To date, it is unclear if this gender difference continues when children enter s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 48 publications
0
17
1
Order By: Relevance
“…Only three were about Greek, one was about Chinese, one was about Italian, one was about Luxembourgish, and one was about Turkish. In particular, the studies on the English language have covered age and gender differences in spatial language skills and relations with math skills (Gilligan-Lee et al 20 21;Bower et al 2020;Johanson and Papafragou, 2014;Ralph et al 2020;Pruden and Levine 2017), the role of language in spatial development (Casasola et al 2020;Miller et al 2020;Cohen and Emmons 2017;Verdine et al 2019), mathematical language (Johnston and Degotardi 2020), parental involvement and support (Ferrara et al 2011;Pruden et al 2011;Thomson et al 2020), and motion events (Johanson et al 2019;Papafragou and Selimis 2010). The Chinese language study examined the Space-Time Metaphor Hypothesis in Early Child Mandarin (Tsung and Wu 2021).…”
Section: Research Gaps: Methodological Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three were about Greek, one was about Chinese, one was about Italian, one was about Luxembourgish, and one was about Turkish. In particular, the studies on the English language have covered age and gender differences in spatial language skills and relations with math skills (Gilligan-Lee et al 20 21;Bower et al 2020;Johanson and Papafragou, 2014;Ralph et al 2020;Pruden and Levine 2017), the role of language in spatial development (Casasola et al 2020;Miller et al 2020;Cohen and Emmons 2017;Verdine et al 2019), mathematical language (Johnston and Degotardi 2020), parental involvement and support (Ferrara et al 2011;Pruden et al 2011;Thomson et al 2020), and motion events (Johanson et al 2019;Papafragou and Selimis 2010). The Chinese language study examined the Space-Time Metaphor Hypothesis in Early Child Mandarin (Tsung and Wu 2021).…”
Section: Research Gaps: Methodological Mattersmentioning
confidence: 99%
“…The results indicated a gender difference in spatial language comprehension, with girls having higher spatial language comprehension than boys. Third, Ralph et al (2020) found that boys outperform girls in psychological rotation development by age 5, and parental language input is one reason. In particular, the mothers used more spatial language with boys than girls in PreK years, whereas more for girls in the post-K years.…”
Section: Gender Differencesmentioning
confidence: 99%
“…A strong predictor of the individual differences in term children's spatial skills is the spatial language they produce. Children's spatial language is in turn related to the parental input they receivefor example, parents' use of spatial language (Pruden et al, 2011;Levine et al, 2012;Polinsky et al, 2017;Ralph et al, 2020). Some children are at a greater risk of falling behind in their spatial skills (Demir-Lira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Parents may also support children’s emerging spatial skills during constructive play by giving feedback, structuring the task, and modeling ways to problem solve during constructive play ( Wood et al, 1976 ; Gauvain et al, 2002 ; Mulvaney et al, 2006 ; Ralph et al, 2020 ; Thomson et al, 2020 ). Children whose mothers provided more support or scaffolding during a spatial task performed better on a cognitive capability test that included measures of spatial ability ( Mulvaney et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we show how we used a videoconference platform (Zoom) to study spatial play at home from a distance, along with the spatial and constructive toys that parents typically choose for their children. The existing studies that have examined children and their parents playing with toys in the home have focused on the relationship between the frequency of spatial play and parent support ( Levine et al, 2012 ), or parent language and children’s performance on spatial tasks ( Mulvaney et al, 2006 ; Pruden et al, 2011 ; Polinksy et al, 2017 ; Ralph et al, 2020 ). Here, we asked a different question.…”
Section: Introductionmentioning
confidence: 99%